1999
DOI: 10.1002/(sici)1099-1573(199909)13:6<504::aid-ptr533>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemic effect of Mangifera indica in rat

Abstract: The leaves of Mangifera indica are used as an antidiabetic agent in Nigerian folk medicine. To determine whether or not there is a scientific basis for this use, the effect of the aqueous extract of the leaves on blood glucose level was assessed in normoglycaemic, glucose - induced hyperglycaemic and streptozotocin (STZ)-induced diabetic rats. The aqueous extract given orally (1 g/kg) did not alter the blood glucose levels in either normoglycaemic or STZ-induced diabetic rats. In glucose - induced hyperglycaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Activation of AGE-RAGE axis is associated with diabetic compliances, as cardiomyopathy and nephropathy. Pulp and leaf extracts of mango produced a significant hypoglycemic effect in streptozotocin (STZ)-induced diabetic rats [25][26][27]. Furthermore, Gondi et al [28] showed that also mango peel extracts have the ability to ameliorate diabetes.…”
Section: Anti-inflammatory Effects Of Mangosupporting
confidence: 93%
“…Activation of AGE-RAGE axis is associated with diabetic compliances, as cardiomyopathy and nephropathy. Pulp and leaf extracts of mango produced a significant hypoglycemic effect in streptozotocin (STZ)-induced diabetic rats [25][26][27]. Furthermore, Gondi et al [28] showed that also mango peel extracts have the ability to ameliorate diabetes.…”
Section: Anti-inflammatory Effects Of Mangosupporting
confidence: 93%
“…However, significant reduction in fasting blood glucose in Moringa oleifera treated rats may suggest hypoglycaemic effect of this leave extract. This finding is similar to the reports of Aderibigbe et al 13 .…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature survey revealed 11 plants having proven antidiabetic properties that are largely distributed across the geographical niche of NE India. The plants include: Ananas comosus (pineapple), Carica papaya (papaya), Catharanthus roseus (noyontara), Citrus aurantium (bitter orange), Cynodon dactylon (bermuda grass), Dioscorea alata (ratalu), Jatropha curcas (barbados nut), Mangifera indica (mango), Morus indica (mulberry), Nelumbo nucifera (lotus), and Tinospora cordifolia (guduchi) (Aderibigbe et al, 1999;Xie et al, 2005;Huralikuppi et al, 2006;Jarald et al, 2008;Sharma et al, 2008;Mishra et al, 2010;Rasineni et al, 2010;Kumar et al, 2010;Maithili et al, 2011;Juarez-Rojop et al, 2012;Sangeetha et al, 2013). Although much progress have been made in recent years in many medicinal plants, the study of genetic potential and improvement through molecular breeding has not been attempted to date for the above mentioned plants.…”
Section: Introductionmentioning
confidence: 99%